2013
DOI: 10.1002/adem.201300218
|View full text |Cite
|
Sign up to set email alerts
|

Brushite and Self‐Healing Flexible Polymer‐Modified Brushite Bone Adhesives for Fibular Osteotomy Repair

Abstract: The study aim was to compare in vitro properties of two experimental bone adhesives (brushite cement and polymer-modified brushite composite) and then assess their in vivo suitability for fixation of a fibular osteotomy using a lapine model. The composite was produced by replacement of the aqueous phase of the brushite cement (800 Â 10 À3 M citric acid) by polypropylene glycol-co-lactide dimethacrylate. FTIR showed this modification enabled pre-mixing and better control of set through light activated polymer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…FTIR spectra between 500 and 4,000 cm − 1 were then obtained using Timebase software with a resolution of 4 cm − 1 every 12 seconds for 30 minutes. The reaction extent ( ) versus time was calculated from the absorbance change ( ) and the maximum absorbance change ( ) at 1565 cm − 1 using the following equation [ 20 ] :…”
Section: Methodsmentioning
confidence: 99%
“…FTIR spectra between 500 and 4,000 cm − 1 were then obtained using Timebase software with a resolution of 4 cm − 1 every 12 seconds for 30 minutes. The reaction extent ( ) versus time was calculated from the absorbance change ( ) and the maximum absorbance change ( ) at 1565 cm − 1 using the following equation [ 20 ] :…”
Section: Methodsmentioning
confidence: 99%
“…ChronOs inject®, PD VitalOs®) for bone lling due to their injectability, biocompatibility degradability and transformation into brushite and then hydroxyapatite in vivo. 25,31,32 Additionally, although PAA has been commercially applied more in dental applications it has also been employed previously in bone repair. 33 A further potential application for the new materials is bone fracture stabilisation.…”
Section: Strength and Modulusmentioning
confidence: 99%
“…Production of more exible cement, by total replacement of the aqueous phase of the brushite cement with a polymer, solved this issue. 32 Furthermore, the study suggested that formation of polyacidic groups (as in polyacrylic acid) could enable "self-repair" of the cement-bone interface as the bone remodels. 32…”
Section: Strength and Modulusmentioning
confidence: 99%
See 1 more Smart Citation